2011
DOI: 10.1242/jeb.053165
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of the scleractinian coral Pocillopora damicornis to bacterial stress from Vibrio coralliilyticus

Abstract: SUMMARYAs the effects of climate change have become increasingly visible over the past three decades, coral reefs have suffered from a number of natural and anthropogenic disturbances that have caused a critical decline in coral populations. Among these disturbances are coral diseases, which have appeared with increasing frequency and severity, often in correlation with increases in water temperature. Although the crucial role played by Vibrio species in coral disease has been widely documented, the scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 100 publications
6
96
0
Order By: Relevance
“…These in situ measurements add a new dimension to existing evidence that some coral pathogens are chemotactic towards coral mucus and other host-derived compounds (Banin et al, 2001;Koren and Rosenberg, 2006;Rosenberg et al, 2007;Meron et al, 2009;Kimes et al, 2011;Vidal-Dupiol et al, 2011;Garren et al, 2014), and that chemotaxis and motility genes can be prominent and dynamic features in the metagenomes of coral-microbial communities (Vega Thurber et al, 2009). Given the strong chemotactic responses that we observed in the laboratory experiments and ISCA deployments, we propose that motility and chemotaxis may be important phenotypes within the context of coralmicrobial interactions.…”
Section: Discussionsupporting
confidence: 53%
“…These in situ measurements add a new dimension to existing evidence that some coral pathogens are chemotactic towards coral mucus and other host-derived compounds (Banin et al, 2001;Koren and Rosenberg, 2006;Rosenberg et al, 2007;Meron et al, 2009;Kimes et al, 2011;Vidal-Dupiol et al, 2011;Garren et al, 2014), and that chemotaxis and motility genes can be prominent and dynamic features in the metagenomes of coral-microbial communities (Vega Thurber et al, 2009). Given the strong chemotactic responses that we observed in the laboratory experiments and ISCA deployments, we propose that motility and chemotaxis may be important phenotypes within the context of coralmicrobial interactions.…”
Section: Discussionsupporting
confidence: 53%
“…This is in stark contrast to the association of temperature and disease state in strain BAA-450; at 27°C BAA-450 causes tissue loss in P. damicornis, whereas bleaching is observed at temperatures of 24 to 25°C (24). It has been suggested that BAA-450 invasion of P. damicornis cells occurs only at elevated water temperatures, perhaps accounting for tissue lysis only at temperatures above 27°C (49). Despite the differences in infection by the two strains, numerous genes encoding proteins that were upregulated in BAA-450 at elevated temperature (26) were also present in OCN008.…”
Section: Discussionmentioning
confidence: 86%
“…Bacterial stress was induced by the addition of V. coralliilyticus at 25°C, whereas bacterial infection was induced by the addition of V. coralliilyticus under conditions of increasing water temperature (from 25 to 32.5°C), which activated bacterial virulence. We recently reported that the bacterium becomes virulent at a temperature of 28°C (27).…”
Section: Stress Protocolmentioning
confidence: 99%
“…However, several recent studies have suggested the involvement of antibacterial agents. Thus, the mucus of several species of scleractinians has been shown to have antibacterial properties (23)(24)(25)(26), and in a recent study on the transcriptomic response of P. damicornis to its specific pathogenic bacterium V. coralliilyticus (27), we identified an mRNA corresponding to a putative antimicrobial peptide (AMP). 3 We describe here the isolation and characterization of damicornin, the first AMP reported from a scleractinian coral.…”
mentioning
confidence: 99%